The fabrication and properties of a flexible sensor based on polyvinylidene fluoride fiber. Issue 19 (October 2022) - Xu, Liyun; Du, Keyuan; Liu, Yuegang; Xie, Kaifang; Tang, Hong; Zhang, Chengjiao
Smart textiles have a wide range of applications in all walks of life. Wearable sensors have become the main research hotspot due to their excellent performance in both perception and response. In this paper, polyvinylidene fluoride (PVDF) was used as the raw material to fabricate continuous fiber via melt spinning method, and β-phase crystal PVDF fiber was obtained at a melting temperature of 230°C and draft ratio of 5. The plain weave fabric of PVDF fiber was dipped into hot dimethyl silicone oil for thermal polarization treatment. When the plate was at a distance of 4 mm, the polarization temperature was 90°C and the polarization voltage was 9 kV, the PVDF had the best polarization property. After polarization, the PVDF fabric showed a good piezoelectric response and a PVDF flexible sensor could be applied to chemical fiber and natural fibers fabrics, in human health monitoring equipment in contact with close-fitting clothing or in home textile products for intelligent alarm systems.